Two-Trait Predictor of Venous Invasion on Contrast-Enhanced CT as a Preoperative Predictor of Outcomes for Early-Stage Hepatocellular Carcinoma After Hepatectomy - Li, Xinming; Zhang, Xuchang; Li, Zhipeng; Xie, Chuanmiao; Qin, Shuping; Yan, Meng; Ke, Qiying; Jin, Xuan; Lin, Ting; Zhou, Muyao; Liang, Wen; Qi, Zhendong; et al. (Frontiers in Oncology, 2021)
Objectives: This study aimed to assess the effectiveness of the two-trait predictor of venous invasion (TTPVI) on contrast-enhanced CT (CECT) for preoperative predicting clinical outcomes in patients with early-stage hepatocellular carcinoma (HCC) after hepatectomy. Methods: This retrospective study included 280 patients with surgically resected HCC who underwent preoperative CECT between 2012 and 2013. CT imaging features of HCC were assessed, and univariate and multivariate Cox regression analyses were used to evaluate the CT features associated with disease-free survival (DFS) and overall survival (OS). Subgroup analyses summarized the hazard ratios (HR) between patients in whom TTPVI was present and absent using a forest plot. Results: Capsule appearance (HR, 0.504, 95% confidence interval [CI], 0.341–0.745, p<0.001) and TTPVI (HR, 1.879, 95% CI, 1.345–2.626, p<0.001) were independent risk factors for DFS, and TTPVI (HR, 2.509, 95% CI, 1.518–4.147, p<0.001), high level of AFP (HR, 1.722, 95% CI, 1.067-2.788, p=0.026) and GGT (HR, 1.787, 95% CI, 1.134-2.814, p=0.026) were independent risk factors for OS. A forest plot revealed that the TTPVI present group had a lower rate of DFS and OS in most subgroups. Patients in whom TTPVI was present in stages I and II had a lower DFS and OS than in those in whom TTPVI was absent. Moreover, there were statistically significant differences in DFS (p<0.001) and OS (p<0.001) between patients in whom TTPVI was absent and present who were classified as Barcelona Clinic Liver Cancer stage A. Conclusions: TTPVI may be used as a preoperative biomarker for predicting postoperative outcomes for patients with early-stage HCC.